NEW FRESHWATER FISH HOSTS OF GORDIIDS (NEMATOMORPHA) LARVAE IN THE SOUTH OF CHILE - Torres-Hevia, Patricio (2021)
Nematomorpha Vejdovsky, 1886 includes most of its species in the taxon Gordiida, presenting a freshwater free-living adult and a parasitic larval stage that live in some aquatic invertebrates, amphibians and fish. Present results documented morphological characteristics of  unencysted and encysted larvae of gordiids in the intestines of two new freshwater fish hosts,  Aplochiton zebra Jenyns, 1842 (Osmeriformes, Galaxiidae) and Trichomycterus areolatus Valenciennes, 1846 (Siluriformes: Trichomycteridae), in the south of Chile.